Regulating Surface and Grain‐Boundary Structures of Ni‐Rich Layered Cathodes for Ultrahigh Cycle Stability. Issue 13 (6th March 2020) - Cheng, Xu; Liu, Meng; Yin, Jingyun; Ma, Chuansheng; Dai, Yanzhu; Wang, Deyu; Mi, Shaobo; Qiang, Wenjiang; Huang, Bingxin; Chen, Yanan
Abstract: The wide applications of Ni‐rich LiNi1‐ x‐y Co x Mn y O2 cathodes are severely limited by capacity fading and voltage fading during the cycling process resulting from the pulverization of particles, interfacial side reactions, and phase transformation. The canonical surface modification approach can improve the stability to a certain extent; however, it fails to resolve the key bottlenecks. The preparation of Li(Ni0.4 Co0.2 Mn0.4 )1‐ x Ti x O2 on the surface of LiNi0.8 Co0.1 Mn0.1 O2 particles with a coprecipitation method is reported. After sintering, Ti diffuses into the interior and mainly distributes along surface and grain boundaries. A strong surface and grain boundary strengthening are simultaneously achieved. The pristine particles are fully pulverized into first particles due to mechanical instability and high strains, which results in serious capacity fading. In contrast, the strong surface and the grain boundary strengthening can maintain the structural integrity, and therefore significantly improve the cycle stability. A general and simple strategy for the design of high‐performance Ni‐rich LiNi1‐ x ‐ y Cox Mny O2 cathode is provided and is applicable to surface modification and grain‐boundary regulation of other advanced cathodes for batteries. Abstract : The capacity and voltage of Ni‐rich LiNi1‐ x ‐ y Co x Mn y O2 cathodes deteriorate during cycling, due to their unstable surface and internal structures. A hybrid architecture (NCM811−NCM424Ti) is found to simultaneously enhance the surface and the grain boundary strength. NCM811−NCM424Ti can keep the mechanical stability in a wide voltage range. The cycle performance of NCM811−NCM424Ti particles is significantly improved due to their structural integrity.